Recent advances in new-onset diabetes mellitus after kidney transplantation - Montada-Atin, Tess (World J Diabetes, 2021)
A common challenge in managing kidney transplant recipients (KTR) is post-transplant diabetes mellitus (PTDM) or diabetes mellitus (DM) newly diagnosed after transplantation, in addition to known pre-existing DM. PTDM is an important risk factor for post-transplant cardiovascular (CV) disease, which adversely affects patient survival and quality of life. CV disease in KTR may manifest as ischemic heart disease, heart failure, and/or left ventricular hypertrophy. Available therapies for PTDM include most agents currently used to treat type 2 diabetes. More recently, the use of sodium glucose co-transporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1 RA), and dipeptidyl peptidase 4 inhibitors (DPP4i) has cautiously extended to KTR with PTDM, even though KTR are typically excluded from large general population clinical trials. Initial evidence from observational studies seems to indicate that SGLT2i, GLP-1 RA, and DPP4i may be safe and effective for glycemic control in KTR, but their benefit in reducing CV events in this otherwise high-risk population remains unproven. These newer drugs must still be used with care due to the increased propensity of KTR for intravascular volume depletion and acute kidney injury due to diarrhea and their single-kidney status, pre-existing burden of peripheral vascular disease, urinary tract infections due to immunosuppression and a surgically altered urinary tract, erythrocytosis from calcineurin inhibitors, and reduced kidney function from acute or chronic rejection.